Effect of strong wind on laminas and petioles of Farfugium japonicum (L.) Kitam. var. japonicum (Asteraceae) - Shiba, Masayuki; Mizuno, Tsukumo; Fukuda, Tatsuya (Frontiers in Plant Science, 2023)
Farfugium japonicum (L.) Kitamura var. japonicum grows mainly in the coastal areas of Japan. Meteorological recording data from natural habitats were used to investigate the factors associated with the laminas and petioles of radical leaves of F. japonicum var. japonicum to avoid or resist higher wind stress. Our morphological and mechanical results indicated that petiole length and petiole cross-sectional area had a weak correlation with wind speed and breaking strength, and the petiole second area moment of inertia did not differ significantly among populations. However, both lamina area and petiole length per petiole cross-sectional area decreased with increasing wind speed, indicating that F. japonicum var. japonicum resisted or avoided an increase in wind speed outdoors by reducing the lamina area and petiole length per petiole cross-sectional area without qualitative changes in their petioles. The results of this study indicated that densely distributed recording stations of the Automated Meteorological Data Acquisition System (AMeDAS) by the Japan Meteorological Agency can be used for environmental adaptation studies of plants in the field using nearby plant populations.